Application of UPFC to Improve the FRT Capability of Wind Turbine Generator - Alharbi, Yasser M.; Yunus, A.M. Shiddiq; Abu-Siada, Ahmed (ETPublishing, 2013)
Variable speed wind turbine generators installation has been significantly increased worldwide in the last few years. Faults at the grid side may call for the disconnection of the wind turbine from the grid as under such events, wind turbine generator (WTG) may not comply with the recent developed grid codes for wind energy conversion systems (WECS). In this paper, a unified power flow controller (UPFC) is applied to improve the fault ride through (FRT) capability of doubly fed induction generator (DFIG)-based WECS during voltage swell and voltage sag at the grid side. Simulation is carried out using MATLAB/Simulink software. Results show that UPFC can effectively improve the FRT capability of DFIG-based WECS and hence maintaining wind turbine connection to the grid during certain levels of voltage fluctuation at the grid side.